Irmãos Koch, think tank, coletivos juvenis: a atuação da rede libertariana sobre a educação - Schiavon, Carolina Rieger Massetti (2020)
The work aims to understand the action of a multidimensional network of institutions and political groups that aim to disseminate a neoliberal ideology acting on the formation of young people, who are seen as new entrepreneurial leaders in search of structural changes in society, and among such changes is the functioning of education. More specifically, it is about perceiving and analyzing the work of the Koch Brothers in organizing a network of institutions and subjects who preach and defend a model of understanding of the neoliberal economy and who are active in Latin America and particularly in Brazil. It aims to analyze the incorporation of corporate, moralizing and privatist discourses in youth circles through the so-called ultra-liberal think tanks. The questions that guide the work are: What is the role of the network funded by the Koch brothers through neoliberal think tanks? How does the relationship between foreign financing, centralized in the political scenario of Brazilian youth movements, with education in mind? What are the institutions and subjects of this network in Latin America? The work has as hypothesis the idea that there is training of think tanks specifically for the formation of young people who start to mirror the ideas of privatization in order to produce either manipulated, or false, or mystical discourses in favor of capital. The documentation used is displayed in archives of institutions involved in the network of relations, websites of youth organizations and political collectives, hyperlinks of universities and Internet products (social networks). Thompson's (1981) theoretical reference of "experience" is used to understand how subjects create new concepts to try to structure a social reality through the organization of apparatuses of circulation and promotion of consciences